771 IMPACT OF NATIONWIDE CENTRALIZATION OF ESOPHAGEAL, GASTRIC, AND PANCREATIC SURGERY ON TRAVEL DISTANCE AND EXPERIENCED BURDEN IN THE NETHERLANDS. (17th September 2021) - Luijten, Josianne; Nieuwenhuijzen, Grard; Sosef, Meindert; Hingh, Ignace; Rosman, Camiel; Ruurda, Jelle; Duijvendijk, Peter; Heisterkamp, Joos; Steur, Wobbe; Laarhoven, Hanneke; Besselink, Marc; Koerkamp, Bas Groot; et al.
Abstract: : This study aims to assess the impact of nationwide centralization of surgery on travel distance and travel burden among patients with esophageal-, gastric-, and pancreatic cancer according to age in the Netherlands. As centralization of care increases to improve postoperative outcomes, travel distance and experienced burden might increase. Methods: All patients who underwent surgery between 2006–2017 for esophageal-, gastric- and pancreatic cancer in the Netherlands were included. Travel distance between patient's home address and hospital of surgery in kilometers was calculated. Questionnaires were used to assess experienced travel burden in a subpopulation (n = 239). Multivariable ordinal logistic regression models were constructed to identify predictors for longer travel distance. Results: Over 23, 838 patients were included, in whom median travel distance for surgical care increased for esophageal cancer (n = 9, 217) from 18 to 28 km, for gastric cancer (n = 6, 743) from 9 to 26 km and for pancreatic cancer (n = 7, 878) from 18 to 25 km (all p < 0.0001). Multivariable analyses showed an increase in travel distance for all cancer types over time. In general, patients experienced a physical and social burden, and higher financial costs, due to travelling extra kilometers. Patients aged >70 years travelled less often independently (56% versus 68%), as compared to patients aged ≤70 years. Conclusion: With nationwide centralization, travel distance increased for patients undergoing esophageal-, gastric-, and pancreatic cancer surgery. Younger patients travelled longer distances and experienced a lower travel burden, as compared to elderly patients. Nevertheless, on a global scale travel distances in the Netherlands remain limited.